CLINICAL BIOCHEMICAL PROFILE AND OUTCOME OF CHOLERA OUTBREAK IN A RURAL POPULATION OF KASHMIR VALLEY NORTH INDIA: A RETROSPECTIVE OBSERVATIONAL STUDY - AHAD, WANI ABDUL; NAIK, MUZAFAR AHMAD; MEHRAJ, SHARIK; ALA, AMAN; SHAFI, AAMIR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to investigate the outbreak of a cholera epidemic that occurred in one of the rural areas of Kashmir valley. Methods: Data were gathered from the medical records for this cross-sectional epidemiological investigation. The inquiry started with the development of a case definition. Line listing, sampling of the patient’s water source and feces, prompt referral, and treatment of those who were vomiting and/or had loose stools were all carried out. Results: About 26 patients that were suspected to have a cholera like illness were line listed, mostly between 20 and 40 years of age with male-to-female ratio being 1.16:1. The case fatality rate was 0%. The source of water supply was river Jhelum in all cases and on sampling the water source it turned out to be unsatisfactory for drinking purposes. Conclusion: Preventive strategies for reducing cholera epidemics can include immunization, improving water conditions, along with the sanitation and hygiene.